Meta-Analysis: The Effect of Prenatal Yoga and the Use of Transcutanal Electric Nerve Stimulation During Pregnancy on Labor Pain - Widyawati, Fiqi; Murti, Bhisma; Adriani, Rita Benya (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Pregnant women are suggested to do light exercise to reduce complaints such as spasms, low back pain, hypertension and other problems. Prenatal yoga and the use of TENS are media that can help reduce pain during labor. The aimed of the study was to analyze the effect of prenatal yoga and the use of TENS during pregnancy on labor pain with a meta-analysis study.Subjects and Method: This was a systematic review and meta-analysis. The study was carried out using PRISMA flow diagrams. Search articles through journal databases including PubMed, Google Scholar, and Science Direct by selecting articles published in 2001-2021. The keywords used were